Evaluation of a rapid antigen detection test (Panbio™ COVID‐19 Ag Rapid Test Device) as a point‐of‐care diagnostic tool for COVID‐19 in a pediatric emergency department. Issue 12 (27th July 2021) - Carbonell‐Sahuquillo, Silvia; Lázaro‐Carreño, María I.; Camacho, Jorge; Barrés‐Fernández, Ana; Albert, Eliseo; Torres, Ignacio; Bretón‐Martínez, José R.; Martínez‐Costa, Cecilia; Navarro, David
Abstract: We evaluated the Panbio™ COVID‐19 Ag Rapid Test Device as a point‐of‐care diagnostic tool for COVID‐19 in 357 patients at a pediatric emergency department. Thirty‐four patients tested positive by reverse transcription polymerase chain reaction, of which 24 were positive by the antigen assay. The sensitivity and specificity of the assay were 70.5% and 100%, respectively. Highlights: The PanBio RAD assay performed well for identifying SARS‐CoV‐2 infected children displaying high viral loads in the upper respiratory tract